2009
DOI: 10.1007/s10544-008-9281-5
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation kinetics of NF-κB in macrophages challenged with pathogens in a microfluidic platform

Abstract: We have developed a microfluidic platform for real-time imaging of host-pathogen interactions and cellular signaling events. Host cells are immobilized in a controlled environment for optical interrogation of the kinetics and stochasticity of immune response to pathogenic challenges. Here, we have quantitatively measured activation of the toll-like receptor 4 (TLR4) pathway in RAW264.7 murine macrophage-like cells. This was achieved by measuring the cytoplasm-to-nucleus translocation kinetics of a green fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…We and others predicted and demonstrated that responses of the NF-κB system to low TNFα doses, as well as low LPS doses, are highly stochastic, and only a fraction of cells exhibit measurable NF-κB activation [27],[34],[74],[75]. Our ELISpot data on 3T3 cells and macrophages show that only a small fraction of cells secrete TNFα.…”
Section: Methodssupporting
confidence: 53%
“…We and others predicted and demonstrated that responses of the NF-κB system to low TNFα doses, as well as low LPS doses, are highly stochastic, and only a fraction of cells exhibit measurable NF-κB activation [27],[34],[74],[75]. Our ELISpot data on 3T3 cells and macrophages show that only a small fraction of cells secrete TNFα.…”
Section: Methodssupporting
confidence: 53%
“…induce NF-κB to translocate from the cytoplasm to the nucleus via phosphorylation and degradation of its cytoplasmic inhibitor IκB. Such process was previously studied in microfluidic devices using fluorescence imaging when the protein of interest was tagged with a fluorescent protein marker20, 21. This translocation process has also been routinely studied by the combination of subcellular fractionation and Western blotting.…”
mentioning
confidence: 99%
“…In the future, we expect that more researchers will turn to classic immune cell types or cell lines that mimic the properties of immune cells, such as the macrophage like RAW 264.7 line [26]. …”
Section: Workflow Methods and Challengesmentioning
confidence: 99%
“…Instead, researchers have now begun to study the NF-κB response to different TNF-α concentrations [10] and time-varying TNF-α stimulation [9, 14, 22]. Recent interests also include the NF-κB activation dynamics under different ligands [13, 18, 23], upon drug perturbations [24, 25], and in response to live or dead bacteria [2629]. Furthermore, multiple outputs can be observed in the same cell through time, for example the dynamics of NF-κB localization and IκBα expression [12, 30].…”
Section: Why Bother With Single Cell Imaging?mentioning
confidence: 99%